Differences in Understanding Basic Social Studies Concepts among Students Reviewed from Learning Motivation and Learning Style Perspectives - Putri, Aurelya Andini; Wijayanti, Inggit Dyaning; Nugroho, Ikhlasul Ardi; Firdaus, Fery Muhamad; Savitri, Sherly Ika (International Journal of Learning Reformation in Elementary Education, 2026)
This study examines differences in students' understanding of basic social studies concepts in the Islamic Elementary Teacher Education Program (PGMI) according to learning motivation and learning styles. A 2×3 factorial quantitative design was employed, and data were analyzed using the Kruskal–Wallis nonparametric test followed by post hoc analysis. The results show that learning motivation does not significantly affect students’ understanding of social studies concepts (p = 0.921 > 0.05). In contrast, learning style has a significant effect (p = 0.037 < 0.05). Further post hoc analysis with a Bonferroni correction reveals a significant difference between the auditory (A2) and kinesthetic (A3) learning styles (p = 0.039 < 0.05). Descriptive findings indicate that students with a kinesthetic learning style achieved higher average scores (95.86) compared to those with an auditory style (89.92). This suggests that kinesthetic learners demonstrate better conceptual understanding. Overall, the findings confirm that motivation level does not differentiate students’ conceptual understanding, while learning styles—particularly kinesthetic—play a significant role. The study highlights the importance of considering diverse learning styles in instructional design to improve students’ conceptual mastery in social studies.